An Application Of Inner Product Spaces " Conditioning And the Rayleigh Quotient " - Aldali, Lutfia (مجلة العلوم الإنسانية والتطبيقية, 2017)
In this paper, we introduce an application on inner product spaces and how used to solve a system of linear equations in the form Ax=b , where A is m×n matrix and b is m×1 vector.